Neutrophil surface adhesion molecule and toll like receptor dynamics in crossbred cows suffering from Staphylococcus aureus subclinical and clinical mastitis - Swain, Dilip Kumar; Kushwah, Mohar Singh; Dang, Ajay Kumar (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The present study was an attempt to delineate the roles played by the neutrophil surface adhesion molecules and toll like receptors (TLRs) in crossbred cows suffering from Staphylococcus aureus subclinical and clinical mastitis. Materials and methods: Thirty six Karan Fries (KF) cows were categorized into three groups namely healthy (n=12), subclinical mastitis (SCM; n=12) and clinical mastitis (CM; n=12) after screening 146 cows. The grouping was done based on evaluation of collected milk samples by routine procedures like Californian Mastitis Test (CMT) scoring, microscopic counting of milk cells (SCC), bacterial culture of milk samples and observing gross changes in milk. Culture of milk and blood was done for the identification of Staphylococcus aureus subclinical and clinical mastitis. Results: Healthy cows expressed significantly (P<0.05) higher L-selectin (CD62L) in both milk and blood neutrophils as compared to the animals suffering from SCM and CM; however, no significant difference was noticed between milk and blood neutrophils. Significant (P<0.05) increase in the expression of beta integrin (CD11b) was observed in the CM group of cows as compared to SCM and healthy cows. Similar trend in the expressions of TLR2 and TLR4 in both blood and milk neutrophils was observed in the CM cows as compared to the healthy and SCM cows. Milk neutrophils revealed a higher expression of TLR as compared to blood neutrophils. Conclusion: Host elicits stage specific expression of surface adhesion molecules and TLR2 and TLR4 as dynamic host innate immune response against Staphylococcal mastitis. http://doi.org/10.5455/javar.2016.c136